Constitutive Theories for Woven Composite Structures Subjected to Shock Loading; Experimental Validation Using a Conical Shock Tube - David R. Hufner (Shock and Vibration)
Woven polymer-based composites are currently used in a wide range of marine applications. These materials often exhibit highly nonlinear, rate dependent, anisotropic behavior under shock loadings. Correlation to transient response data, beyond an initial peak, is often difficult. The state of damage evolves throughout the time history and the unloading response varies based on the amount, and nature of, the accumulated damage. Constitutive theories that address the loading and unloading responses have been developed and integrated with each other. A complete theory, applicable to transient dynamic analysis, is presented. The model is implemented within the commercial finite element code, Abaqus, in the form of a user material subroutine. In this study, the conical shock tube is used to experimentally reproduce the high strain rates and fluid structure interactions typical of underwater shock loadings. The conical shock tube data is used to validate analytical model predictions. Simulation results are in good agreement with test data.